Who are the Essential and Frontline Workers? - Francine D. Blau; Josefine Koebe; Pamela Meyerhofer (Institute of Labor Economics (IZA), 2020)
Identifying essential and frontline workers and understanding their characteristics is useful for policymakers and researchers in targeting social insurance and safety net policies in response to the COVID-19 crisis. We develop a working definition that may inform additional research and policy discussion and provide data on the demographic and labor market composition of these workers. In a three-step approach, we first apply the official industry guidelines issued by the Department of Homeland Security (DHS) to microdata from the 2017 and 2018 American Community Survey to identify essential workers regardless of actual operation status of their industry. We then use data on the feasibility of work from home in the worker's occupation group (Dingel and Neiman 2020) to identify those most likely to be frontline workers who worked in-person early in the COVID-19 crisis in March/April 2020. In a third step we exclude industries that were shutdown or running under limited demand at that time (Vavra, 2020). We find that the broader group of essential workers comprises a large share of the labor force and tends to mirror its demographic and labor market characteristics. In contrast, the narrower category of frontline workers is, on average, less educated, has lower wages, and has a higher representation of men, disadvantaged minorities, especially Hispanics, and immigrants. These results hold even when excluding industries that were shutdown or operating at a limited level.
Keywords: J15; J16; J21; 330; COVID-19; essential workers; frontline workers; gender; race differences; hispanics; immigrants